(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In this article the threats in the region and regional challenges are analyzed. The authors stress the role of Kazakhstan in providing regional security and integration process expansion. Crucial role is playing the initiatives of the President of the Republic of Kazakhstan Nursultan Nazarbayev to create regional security, concerning policies of the major players the U.S. A., Russia and China. Keywords: regional security, integration processes, threats, Central Asia.